Successful treatment of herpes simplex-associated erythema multiforme with a combination of acyclovir and prednisone - Arny E. Muryah; Irna Sufiawati (Journal of Dentomaxillofacial Science, 2017)
Objective: Erythema Multiforme (EM) is an acute mucocutaneous hypersensitivity reaction triggered by certain infections and medications. EM induced by virus infection termed as Herpes- associated Erythema Multiforme (HAEM). The use of corticosteroids for treating HAEM has been a long debate issue. The aim of this case report is to present a patient with HAEM who was successfully treated with acyclovir combined with prednisone.Methods:A 31-years-old female, presented with a complaint of pain and diffuse ulcers in mouth. The patient reported recurrent episode of the ulcers of the mouth during the last two years. On extra oral examination, lips were crusted and bleeding. Intraoral examination revealed multiple diffuse ulcerations on mucosa. Nolesions were seen in other part of the body. Laboratory investigation revealed normal complete blood count and positive HSV-1 serology. The patient was diagnosed as HAEM.The patient was treated with acyclovir (1000 mg/day) and prednisone (10mg/day), topical mixture corticosteroid, chlorhexidine gluconate 0.2% and multivitaminduring seven days.Results:All lesions healed without any further clinical sequelae within 7 days.The clinical success of corticosteroids as effective anti-inflammatory agents is largely attributed to their ability to reduce the expression of pro-inflammatory genes, help to maintain vascular integrity and decrease the expression of leukocyte adhesion molecules.Conclusions:The addition of prednisone to acyclovir for HAEM resulted in a significant reduction of clinical signs and symptoms during the first week. The combination of acyclovir and corticosteroids may play an important role in the standard care for HAEM.